Dampak UMKM Pempek Terhadap Pertumbuhan Ekonomi Kota Palembang: Peluang dan Tantangan - Saputri, Heni; Zahrani, Tyara; Pusri, Desy; Wanda Haliza, Nadya; Panorama, Maya (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
Pempek is a typical food of Palembang City that not only has high cultural value, but also plays a significant role in driving regional economic growth through Micro, Small, and Medium Enterprises (MSMEs). Pempek MSMEs make a real contribution to Palembang's Gross Regional Domestic Product (GRDP), with contributions from the food processing industry sector reaching around 7-10% during the 2022-2024 period. In addition to creating jobs for thousands of local people, these MSMEs also drive other economic sectors such as logistics, trade, and tourism. Great opportunities are open through local food consumption trends, government support, and the use of digital technology that allows for wider marketing. However, pempek MSME actors also face challenges such as limited capital, tight competition, constraints on distribution outside the region, and the low utilization of technology evenly. Therefore, by strengthening innovation, business training, and policy support, pempek MSMEs have the potential to continue to grow and become a pillar of the creative economy of Palembang City.